Wojewódzki Zjazd Chłopów w Gdańsku. (Gdańsk : [s.n.], 1946)
Afisz z programem zjazdu, który miał miejsce w Stoczni Gdańskiej 29.08.1946 r.
Keywords: Gdańsk (Polska) -- 1945-1970 -- druki ulotne; Gdańsk (Polska) -- 1945-1970 -- plakaty; Gdańsk (Polska) -- 1945-1970 -- źródła